PENINGKATAN KINERJA, MITIGASI RISIKO DAN ANALISIS KELEMBAGAAN PADA RANTAI PASOK CABAI MERAH DI KABUPATEN GARUT - Maulida Hayuningtyas; Marimin; Indah Yuliasih (Jurnal Teknologi Industri Pertanian, 2020)
Supply chain of red chilli has not integrated and involves all actor like farmers, collectors, traders, suppliers and industry. This condition creates instability in the quality of red chilli on the market, supply availability and price fluctuations. The purpose of this research was to study the mechanisms, performance, risk mitigation and institusional analysis of the supply chain using the Van de Vorst method, SCOR-AHP method, House of Risk (HOR) and Interpretative Structural Modeling (ISM). The location of this study was in Garut District, the highest production of red chili in West Java. The supply chain mechanism was approached through four elements, namely a) supply chain structure, b) chain business processes, c) network management and chain coordination, and d) chain resources used. The supply chain performance system has five levels of hierarchy, namely goals, business processes, criteria, attribute, and performance metrices. Results showed that the supply chain performances of the red chilli at farmers, collector, suppliers, and small medium enterprise (SME) were 74.6%, 76.8 %, 82.5%, 81.9%, respectively. Risk priorities showed there were 10 at the farmer, 9 at the traders, 11 at the supplier, and 10 at the industrial stage. Information on supply chain performance is expected to enable actors in the red chili supply chain to improve coordination, integration between actors, fulfillment of production facilities, proper implementation of Good Agricultural Practices (GAP), and distribution mechanisms, so that can optimally fullfil the consumer demand and minimize yield loss to improve competitiveness in the red chili industry. Keywords : Supply chain, performance, risk mitigation, institutional analysis